A cross-sectional study investigating frequency and features of definitely diagnosed diabetic painful polyneuropathy. Issue 12 (December 2018) - Truini, Andrea; Spallone, Vincenza; Morganti, Roberto; Tamburin, Stefano; Zanette, Giampietro; Schenone, Angelo; De Michelis, Chiara; Tugnoli, Valeria; Simioni, Valentina; Manganelli, Fiore; Dubbioso, Raffaele; Lauria, Giuseppe; et al.
Abstract : Abstract: This cross-sectional multicentre study aimed at investigating frequency and features of painful diabetic polyneuropathy. We consecutively enrolled 816 patients attending hospital diabetic outpatient clinics. We first definitely diagnosed diabetic polyneuropathy and pure small-fibre polyneuropathy using clinical examination, nerve conduction study, and skin biopsy or quantitative sensory testing. Adhering to widely agreed criteria, we then identified neuropathic pain and diagnosed painful polyneuropathy using a combined approach of clinical examination and diagnostic tests. Of the 816 patients, 36% had a diabetic polyneuropathy associated with male sex, age, and diabetes severity; 2.5% of patients had a pure small-fibre polyneuropathy, unrelated to demographic variables and diabetes severity. Of the 816 patients, 115 (13%) suffered from a painful polyneuropathy, with female sex as the only risk factor for suffering from painful polyneuropathy. In this large study, providing a definite diagnosis of diabetic polyneuropathy and pure small-fibre polyneuropathy, we show the frequency of painful polyneuropathy and demonstrate that this difficult-to-treat complication is more common in women than in men. Abstract : Supplemental Digital Content is Available in the Text.This epidemiological study in 816 patients with diabetes shows that 13% suffered from a painful polyneuropathy, with female sex as the predominant risk factor.